PEMBUATAN MODEL ALAT PENGASAPAN IKAN LAUT PADA MASYARAKAT NELAYAN PANTAI TRISIK KABUPATEN KULON PROGO DIY - Lastariwati, Badraningsih (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
The vucer program was aimed to realize a tool for smoking fish using liquid smoke techniql;1pwhich perforins optimal work, easy to use and maintain affordable, ergonimic and efficient.'Theprogram    was started  from July to November  2002. The partner  of thisprogram  was  the  fishermen  group under  TPI  Mian  Samudra,  Trisik  Beach,  Kulon Progo, Yogyakarta .. T~~l activity was begun  by making a tool for smooking  fish, a specially  designed'oven,    then followed   with  the  experiment  of  the  tool  in  thelaboratory ofPKK-Bog~,  UNY.   'By creating a new tool to process  smoked fish, it is hoped that it can producegood quality and quantitysmeked  fish,  as well as can save time and energy. With this tool, it means that it gives an opportunity for an industry to develop its product. Then it can increase the fishermen arid fish sellers'  income.The product yielded from this program was a set of oven for smoking fish which is strong enough, easy to operate, with sufficie volume and simple quality control.Key words:  fish smoking, smoked fish, and tool model